COMPARATIVE ANALYSIS OF GASTROINTESTINAL PARASITES IN FISH FROM KADUNA RIVER AND SELECTED DOMESTIC PONDS IN KADUNA METROPOLIS (FUDMA JOURNAL OF SCIENCES, 2024)
Fish is a source of livelihood for fishermen and fish farmers especially in Nigeria and other developing countries. Fish from river and domestic ponds are widely consumed today, hence the need to conduct this study to enable monitoring and adopting control measures of parasites. The aim of this research to analyze the gastrointestinal parasites in fish from Kaduna River and selected domestic ponds in Kaduna metropolis. Results showed that 197 fishes out of the 350 examined were infected, giving an overall prevalence (56.3%) in fish from Kaduna River and selected domestic ponds. Infection was significantly higher in fishes from Kaduna River (68.0%) than in those from selected domestic ponds (27.0%). The male was 68.3% significantly higher (p < 0.05) than that of the female (23.1%) and there was significant association (p < 0.05) in the prevalence of gastrointestinal parasites and weight of fish sampled from Kaduna River and selected domestic ponds. Intestines harboured the highest number of parasites (168) than stomach and parasites identified comprised of three taxonomic groups, the nematodes were Capillaria species, Paracamallanus species, Contracaecum species and Camallanus species respectively. Cestode was Diphyllobothrium latum and Trematode was Clinostomum species. There was no significant difference (p > 0.05) of intensity and parasite load to the fish species of parasites identified from River Kaduna and selected domestic ponds. The study has revealed that different parasites in fresh water fish from Kaduna River constitutes a major threat to fish productivity than the selected domestic ponds. It is recommended that...
Keywords: Domestic ponds; Fish species; River